2022
DOI: 10.3389/fcimb.2022.1040765
|View full text |Cite
|
Sign up to set email alerts
|

Smoking by altering the peri-implant microbial community structure compromises the responsiveness to treatment

Abstract: Smoking is an essential risk factor for peri-implant diseases. It also hampers the clinical outcomes of peri-implant therapies. Nonetheless, the effect of smoking can go undetected until the emergence of clinical signs. Bacterial-induced inflammation is responsible for the initiation and progression of peri-implant diseases. We hypothesize that smoking impacts the peri-implant microbiome even in status of clinical health, putting it into a sub-healthy condition that responds poorly to peri-implant treatments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
0
0
1
Order By: Relevance
“…Os dois fatores etiológicos principais que levam a essa perda são: o trauma oclusal e a contínua agressão microbiológica, que acarretam uma resposta inflamatória do tecido conjuntivo periimplantar com perda óssea progressiva (Monje et al, 2022;Zhang, et a, 2022).…”
Section: Resultsunclassified
“…Os dois fatores etiológicos principais que levam a essa perda são: o trauma oclusal e a contínua agressão microbiológica, que acarretam uma resposta inflamatória do tecido conjuntivo periimplantar com perda óssea progressiva (Monje et al, 2022;Zhang, et a, 2022).…”
Section: Resultsunclassified
“…It promotes the early acquisition and colonisation of biofilm-forming pathogens, leading to a disease-associated peri-implant microbiome, even in clinically healthy individuals [56,57]. Metagenomic sequencing has revealed that other differences in the peri-implant microbiome in smokers include greater stability and resilience, and more coordinated microbial interactions, which have adverse effects on disease pathogenesis and responsiveness to therapy [58]. The biological effects of smoking include alterations to the microvasculature and suppression of the immune system, which inhibits the vascular response to bacterial plaque [59,60].…”
Section: Smoking and Diabetes Mellitusmentioning
confidence: 99%